Unifikovanij algoritm kompleksnogo kontroljupidgotovlenosti sportsmeniv u komandnih sportivnih igrah - Mitova, O. (Science in Olympic Sport, 2019)
Objective. To substantiate a unified control algorithm based on the analysis of modern tendencies of competitive and training activities of athletes in team sports games, that could be used at various stages of long-term preparation. Methods. Analysis of special scientific and methodological literature, survey, pedagogical observation, systematic method, data generalization and systematization. Results. A unified complex control algorithm in team sports games has been developed, which consists of four stages: organizational, diagnostical, evaluational, correctional. Principal differences from analogues in the approach and the development of the algorithm are such components as the adequacy of control tasks to those of a specific stage of long-term preparation; selection of informative tests with account for sensitive periods of development of physical qualities, specific abilities (sense of time, spatial orientation, ball sense, etc.), the studied material for technical, tactical and theoretical fitness; assessment of psycho-physiological state of players; evaluation of the status of interpersonal relationships in the team; distribution of evaluation of competitive activity into individual, group and team indices; expansion of the range of criteria for competitive activity evaluation; terms of control realization with account for the competition calendar. Conclusion. Unifi ed algorithm of complex control for fitness can be used at various stages of long-term preparation in various types of team sports games for timely detection of weak and strong points followed by subsequent correction of training and competitive activities of individual athletes, group of players, and the entire team.